2006
DOI: 10.1093/molehr/gal024
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of vascular endothelial growth factor in severe pre-eclampsia

Abstract: Several lines of evidence support the hypothesis that vascular endothelial growth factor (VEGF) plays an important role in the pathogenesis of pre-eclampsia (PE). VEGF is a key component in the regulation of vascular remodelling and the survival of cytotrophoblasts in the placenta. In this case-control study, we aimed to test whether VEGF genetic polymorphisms are associated with the risk of severe PE. We enrolled 84 nulliparous pregnant women with severe PE (PE group). Their VEGF G(+405)C and VEGF C(-2578)A g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 22 publications
3
62
1
7
Order By: Relevance
“…In the HSP72 gene, Fekete et al (31) found that VLBW infants homozygous for the G allele were at increased risk for AKI (OR ϭ 3.17, P Ͻ 0.01). This same group also found that for the VEGF Ϫ2578 C/A polymorphism, VLBW infants homozygous for the A allele were protected against AKI (OR ϭ 0.2, P ϭ 0.021) (29).…”
Section: Other Genesmentioning
confidence: 76%
“…In the HSP72 gene, Fekete et al (31) found that VLBW infants homozygous for the G allele were at increased risk for AKI (OR ϭ 3.17, P Ͻ 0.01). This same group also found that for the VEGF Ϫ2578 C/A polymorphism, VLBW infants homozygous for the A allele were protected against AKI (OR ϭ 0.2, P ϭ 0.021) (29).…”
Section: Other Genesmentioning
confidence: 76%
“…4 Analysis of genetic variations of fetuses showed two SNPs with significant difference 1) RENIN (rs11240688) (Chi-square= 9.673, p=0.002) with OR=3.042 (CI is 1.476 to 6.267).…”
Section: -17mentioning
confidence: 97%
“…Banyasz et al found carriers of allele VEGF G405C occurred less frequently in pre-eclampsia than in controls and that the progression of preeclampsia may be modified by the presence of VEGF 2578A allele. 4 Shim et al (2007) evaluated the distribution of +936 C/T polymorphism in VEGF gene in Korean women and found that its carriage may be associated with increased susceptibility to the development of PE and may be an independent risk factor. 5 Preeclampsia presents a peculiar challenge, in that both the maternal and fetal genotype may contribute to the clinical phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Генотипирование Генотипирование полиморфизмов промо-торного региона генов VEGF -2578 (rs 699947), ММР3-1171 (rs 3025058), ММР9-1562 (rs 3918242), TNFα-863 (rs1800630), TNFα-308 (rs1800629), TNFα-238 (rs 361525) осуществляли методом ре-стриктазного анализа продуктов амплификации (ПДРФ-анализ), с использованием специфич-ных праймеров [5,6,21,26,29] Статистический анализ При статистическом анализе результатов ис-следований использовали такие показатели, как частота встречаемости генотипов, отноше-ние шансов (OR) с расчетом 95% доверительного интервала (OR 95%CI). Расчет величины OR про-водили по методу Вульфа-Холдейна [1].…”
Section: пациентыunclassified